1975
DOI: 10.1111/j.1432-1033.1975.tb04069.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidences for a Sulfhydryl Group in the ATP-Binding Site of (Na+ + K+)-Activated ATPase

Abstract: 5,5'-Dithio-bis(2-nitrobenzoate) inhibited (Na' + K+)-activated ATPase by affecting the Nafdependent phosphorylation reaction. ATP and ADP but not ITP protected the enzyme at low concentrations against the inactivation.The ATP analogues 6-mercaptopurine riboside-5'-triphosphate and S-(2,4-dinitrophenyl)-6-mercaptopurine riboside-5'-triphosphate inactivated (Na+ + K+)-ATPase whereas the respective monophosphates left the enzyme unaffected. S-(2,4-Dinitrophenyl)-6-mercaptopurine triphosphate inactivated the part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1976
1976
1998
1998

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…In skeletal muscle, these ATP-sensitive K ÷ channels can be inhibited by intracellular application of reagents that modify SHgroups, and it has been shown that the functionally important sulphydryl group is likely to be near the ATPbinding site of the channel (Weik and Neumcke 1989 a). A similar arrangement of an essential SH-group in the ATPbinding site has previously been inferred for the Na ÷, K+-ATPase (Patzelt-Wenczler et al 1975). This analogy between the ATP-sensitive K + channel and the Na ÷, K ÷-ATPase stimulated the experiments described in this paper.…”
Section: Introductionsupporting
confidence: 50%
“…In skeletal muscle, these ATP-sensitive K ÷ channels can be inhibited by intracellular application of reagents that modify SHgroups, and it has been shown that the functionally important sulphydryl group is likely to be near the ATPbinding site of the channel (Weik and Neumcke 1989 a). A similar arrangement of an essential SH-group in the ATPbinding site has previously been inferred for the Na ÷, K+-ATPase (Patzelt-Wenczler et al 1975). This analogy between the ATP-sensitive K + channel and the Na ÷, K ÷-ATPase stimulated the experiments described in this paper.…”
Section: Introductionsupporting
confidence: 50%
“…2), is compatible with the assumption that thi0J groups associated with different effects could be embedded in a matrix of varied lipophilicity. Thus, Hg-sensitive thi01 groups instrumental to membrane transport appear to be located at the inner surface of the membrane or at least not to be readily accessible from the outside (neuronal Na-K. ATPase: Patzelt-Wenczler et al 1975; renal sodium tran~ port: Ullrich et al 1973; erythrocyte nucleoside transport: Tse et al 1985). The orientation of thiol groups in the membrane, the prevalence of inotropic effects in relation to lipophilicity and the role of permeation can be combined in a model in which lipophilic mercurials concentrate in the membrane and there bind mainly to SH-groups responsible for the negative inotropic action.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, by calorimetric measurements, only conformational changes which are accompanied by enthalpy changes can be found. With SH reagents, probably structural changes in the vicinity of the ATP binding site(s) are detected because there is some evidence that a sulfhydryl group may exist in the ATP binding site(s) [19]. By ouabain binding or ouabain inhibition studies, only structural changes in the vicinity of the ouabain binding site(s) can be sensed.…”
Section: Effect Of Mg ++ and Phosphate On The (Na+-k+)-a Tpase Structurementioning
confidence: 98%